PENGARUH MINAT BELAJAR DAN FASILITAS BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI SISWA KELAS X IPS DI SMA NEGERI 2 PEKANBARU - Fransiska Nahampun; Gimin '; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research in SMA Negeri 2 Pekanbaru to know the influence of learning interest and learning facilities to the learning result of economic subjects of class X IPS in SMA Negeri 2 Pekanbaru. Learning outcomes are influenced interest learning and learning facilities. The population in this research are 145 students and sampling technique in this research using simple random sampling technique is slovin formula produce 59 sample people. Technique of collecting data is through questionnaire technique while type and sources of data that is primary data and secondary data. Further data were analyzed using multiple regression analysis, simultaneous regression coefficient test (F test), partial correlation test, and coefficient of determination (R2). The results showed that the variables of learning interest and learning facilities simultaneously affect the learning outcomes. This means that the independent variables to equal affect the dependent variable. Furthermore, based on the partial correlation test can be seen that only the variable interest in learning that affects the results of learning is indicated by significance 0,026 whereas learning facility variables don’t have effect. With coefficient value of determination equal to 0,140. It means that the contribution of independent variable to the dependent variable is 14%. While the remaining 86% is determined by other variables such as motivation, talent, intelligence, school learning facilities, family environment and school environment that is not researched. Based on the results of research, suggestions or recommendations of researchers is that students should be able to increase interest in learning and use of learning facilities that are available with good or maximal so that learning outcomes can be achieved properly.Keywords : learning facilities , interest in learning , learning outcomes